Analisis Tingkat Maturitas Implementasi Manajemen Risiko di IPB University - Ryandi Simanjuntak; D S Priyarsono; Titik Sumarti (IPB University, 2021)
The implementation of risk management will not always achieve its goals. This problem can be caused by lack of consistency during the risk management implementation or it can not adapt to environmental changes. Therefore, an organization needs to measure the maturity level of the organization’s risk management implementation. This research aims to analyze the maturity level of risk management implementation at IPB University. The research was conducted at IPB University, and it was using primary and secondary data. Research shows that the characteristics that need to be measured, or the attributes that need to be measured, in measuring the maturity level of risk management implementation at IPB University are risk culture, risk management framework, risk management process and risk management documents. The attributes will have their indicators, parameters, and test factors. The result of the measuring of maturity level of risk management implementation at IPB University indicates that risk management at IPB University has been implemented systematically and the implementation has referred to the standard consistently and comprehensively. Risk management has begun to be integrated to organization governance and management. The risk management competence, leadership, and commitment are starting to expand through the organization but the positive attitudes in managing risk is still tend to be limited.